A nonparametric procedure for exploring differences in rating quality across test-taker subgroups in rater-mediated writing assessments. (October 2019) - Wind, Stefanie A.
Differences in rater judgments that are systematically related to construct-irrelevant characteristics threaten the fairness of rater-mediated writing assessments. Accordingly, it is essential that researchers and practitioners examine the degree to which the psychometric quality of rater judgments is comparable across test-taker subgroups. Nonparametric procedures for exploring these differences are promising because they allow researchers and practitioners to examine important characteristics of ratings without potentially inappropriate parametric transformations or assumptions. This study illustrates a nonparametric method based on Mokken scale analysis (MSA) that researchers and practitioners can use to identify and explore differences in the quality of rater judgments between subgroups of test-takers. Overall, the results suggest that MSA provides insight into differences in rating quality across test-taker subgroups based on demographic characteristics. Differences in the degree to which raters adhere to basic measurement properties suggest that the interpretation of ratings may vary across subgroups. The implications of this study for research and practice are discussed.